(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: In recent decades, antibiotic resistance of pathogenic bacteria has become a top concern in the health sector of many countries, including Vietnam. Objectives: Describe the current situation of antibiotic use on surgical patients at Thai Binh General Hospital in 2020. Methods: Cross-sectional survey, quantitative research. Results: 100% of patients use antibiotics after surgery. None of the patients were using a prophylactic antibiotic regimen. The antibiotic group most used is beta-lactam, of which Cephalosporin generation 3 accounts for 87.4% and 46,9% was 5-nitro-imidazoles.